Street-level and government-level Islamophobia in the Visegrád Four countries. (20th October 2018) - Hafez, Farid
ABSTRACT: Islamophobic mobilization has become a crucial aspect of right-wing populist mobilization. Hafez's article focuses on the case of the Visegrád Four countries: Poland, Czech Republic, Slovakia and Hungary. Based on reportedly widespread hostility against Muslims among the population in this region, one would assume a large potential for street-level activism analogous to the German Pegida. Yet, attempts to organize grassroots Islamophobic movements have not been particularly successful in the Visegrád Four. Using social movement theory, Hafez explains this by the fact that the issue of Muslim migration has been appropriated by the ruling parties, leaving little opportunity for independent grassroots mobilization.